Exploring student residences: Impact of parental education on residence experiences - Justino, E.; Silva, S. F. da; Mauritti, R; Belchior-Rocha, H. (EDULEARN24 Proceedings, 2024)
The degree of education of students' parents has a significant impact on students' judgments and various aspects of their experience. It also significantly impacts their reasons for living in a student residence. This article aims to discuss the students' place of origin and social backgrounds, as informed by their parents' levels of education, and how this influences their relationship with student residences, namely in the assessment and facilities for study. The data collected was based on an online survey of students displaced from their usual home to pursue their studies. A total of 1021 students were surveyed. Of these, the vast majority (around 79%) are staying in a student residence, and around 4% are past residents. The multivariate analysis (e.g., cluster analysis) of the characteristics of these students results in three standard profiles. The first pertains to female students from Portugal less than 22 years old from outlying areas of large and medium-sized cities with parents who have finished high school. The second profile consists of males from urban areas with parents who have completed higher education. The third profile consists of students aged between 22 and 23 from rural areas and whose parents have only completed primary school. The analysis revealed some significant variations in students' subjective experiences according to their parents' level of education. Differences in perceptions and experiences of living conditions were found in terms of the search for housing, payment conditions and difficulties, perceptions of safety, comfort and sharing a living space with other students.